Komunikasi Represif pada Spanduk Larangan Pencemaran Lingkungan - Pohan, Syafruddin (Universitas Muhammadiyah Sumatera Utara, 2023)
The City Government (Pemko) of Medan prohibits every person or entity from littering as stated in the Mayor’s Regulation (Perwal) Number 6 of 2015 with sanctions of imprisonment and/or fines. Even so, it can be seen around Street Letda Sujono, Medan Tembung, Medan City, several waste dumping points as proof of the society ignocancy. One of the outreach efforts that can be carried out by local officials or participants is to put up warning banners contains rules and criminal sanctions message for violators. This research is based on Max Weber's Bureaucratic Theory, Lasswell's communication formulation, and Ruben and Steward's public communication perspective. Using Observation and interviews in collecting data then the data is tested for validity using Conscientization which will produce historical situation (ideography) and untiy theory and Praxis. The results of the research show that (1) There are 12 trash dumps in one part of the Bandar Selamat sub-district, the largest of which is located in Sector VII, (2) There is an unwritten schedule of the violator who tend to leave trash bags during the cleaning staff's operating hours, (3) The Village Head and Sector VII Head (Kepling VII) have carried out a series of prevention and maintenance efforts as instructed by the Medan Tembung Subdistrict Head, but no significant changes have been found. (4) The feedback of the residents of Sector VII regarding the banner with the message